Stereotypes and Prejudices. From Social Sciences to Semiotics - Cosenza, Giovanna (E|C, 2023)
This paper draws from the social sciences the notion of stereotype, as it relates specifically to people and social groups, by surveying how, from the 1950s to the present, social psychology has elaborated and discussed it in a systematic and empirically grounded way. It then distinguishes stereotypes and prejudices, showing how stereotyping and categorization follow similar processes, and how it is necessary to acknowledge, not only in scholarship but in social practice, the unavoidability of stereotypes, in order to overcome them and prevent them from leading to discriminatory attitudes. Finally, some concepts from Umberto Eco’s interpretive semiotics and Algirdas J. Greimas’ generative semiotics are proposed, which the author believes are most helpful in setting up a semiotic analysis of stereotypes that can empirically and operationally dialogue with both social psychology and social semiotics.